Chapter Traduire en français le lexique du patrimoine artistique de la ville de Bologne : le sous-corpus comparable BER du projet LBC - Zotti, Valeria (Lessico multilingue dei Beni Culturali, 2023)
This chapter presents a new tun in the research project Multilingual Cultural Heritage Lexicon that consists in extending the LBC French corpus through a sub-corpus on Bologna and the Emilia-Romagna region (BER). After presenting the two projects connected with the LBC corpus (UniCittà 2019-2021 and UniVOCittà - ongoing), Zotti presents the BER sub-corpus from a quantitative and qualitative point of view reflecting on its role ans its complementarity for the description of the artistic terminology in the LBC comparable monolingual corpus. Zotti concludes by showcasing the applications and results of the corpus-driven approach and its potential for inferring linguistic knowledge when it comes to (diastratic and diatopic) synonymy, suggesting new strategies for the translation of cultural-specific items.